Considerations when starting patients on multiple biologics and small molecules. Issue 6 (15th November 2022) - Vuyyuru, Sudheer K.; Kedia, Saurabh; Ahuja, Vineet
Abstract : Purpose of review: Inflammatory bowel disease (IBD) is complex disease that poses significant economic, and psychological burden on patients. Despite advent of newer biologics and small molecules targeting different aspects of immunopathogenesis, there appears to be a plateau in clinical outcomes. In this review we discuss the role of multiple biologics, existing evidence and various considerations when prescribing multiple biologics. Recent findings: Recent scientific advances helped to unravel the pathophysiology of inflammatory bowel disease and newer cytokines have been identified which can be potential targets in the management of IBD. Targeting more than one cytokine appears to be logical solution to break the therapeutic ceiling to improve clinical outcomes in IBD. The combination biologics appear safe and effective; however, the available evidence is limited. Refractory IBD, presence of other immune mediated inflammatory diseases and extra intestinal manifestations are currently the common considerations of combination biologics in IBD. Summary: Inflammatory bowel disease is a complex immune mediated disease with diverse clinical presentation and often has a complicated clinical course requiring multidisciplinary management. As the number of targeted therapies increases so does the concern on their safety and efficacy. Combination biologics though may appear to be safe, we need well designed prospective studies for firm conclusions.